2006
DOI: 10.1080/02652030500442516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mechanical shelling and dehulling onFusariuminfection and fumonisin contamination in maize

Abstract: Mechanical shelling and dehulling methods were tested to evaluate their impact on Fusarium infection and fumonisin contamination in maize. All shelling methods which were tested were found to damage the grains. The IITA sheller caused the highest level (up to 3.5%) of damage. Fusarium populations were higher on damaged grains, the highest being recorded from grains damaged by the IITA sheller (2,533.3 cfu g(-1)). Fumonisin levels were higher in damaged grains, the highest being in maize shelled with the IITA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 9 publications
(7 reference statements)
1
33
0
1
Order By: Relevance
“…It is worth to note that FB exposure data generated by this and other [25,33] studies that used contamination data for unmilled maize might have been overestimated. This is because in the course of milling, maize undergoes a dehulling step that is known to reduce FB contamination in the consumed fraction; the flour [25,37,38].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is worth to note that FB exposure data generated by this and other [25,33] studies that used contamination data for unmilled maize might have been overestimated. This is because in the course of milling, maize undergoes a dehulling step that is known to reduce FB contamination in the consumed fraction; the flour [25,37,38].…”
Section: Discussionmentioning
confidence: 93%
“…This is because in the course of milling, maize undergoes a dehulling step that is known to reduce FB contamination in the consumed fraction; the flour [25,37,38]. Therefore, use of contamination data determined in ready-to-cook maize flour or ready-to-eat complementary food would generate better estimate of the FBs exposure in this community.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was previously reported that aflatoxin and fumonisin was related to storage structures (Hell et al, 2010;Fandohan et al, 2005), insect infestation (Udoh et al, 2000;Hell et al, 2000;Fandohan et al, 2005), length of storage time (Orsi et al, 2000;Egal et al, 2005), climatic conditions Milani, 2013), sorting (Hell and Mutegi, 2011), Drying methods (Atukwase et al, 2009). …”
Section: Total Aflatoxin and Fumonisin Contamination In Storage Beansmentioning
confidence: 99%
“…Furthermore, single factor and orthogonal experiments were performed to determine the optimal operating parameters of the bionic threshing device (Fandohan et al,2006;Li et al, 2014;.…”
mentioning
confidence: 99%